2022
DOI: 10.1177/18333583221133465
|View full text |Cite
|
Sign up to set email alerts
|

Individual and contextual factors in the Swedish Nutrition Care Process Terminology implementation

Abstract: Background Standardised terminologies and classification systems play an increasingly important role in the continuous work towards high quality patient care. Currently, a standardised terminology for nutrition care, the Nutrition Care Process (NCP) Terminology (NCPT), is being implemented across the world, with terms for four steps: Nutrition Assessment (NA), Nutrition Diagnosis (ND), Nutrition Intervention (NI) and Nutrition Monitoring and Evaluation (NME). Objective To explore associations between individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Payton et al (2023) reported the need for balance between structured and narrative forms of documentation and that highly structured formats (a feature of EHRs) can limit usability. Several authors highlighted multifactor influences on CDI, including personal, systemic and environmental (Jebraeily et al, 2023; Lövestam et al, 2022; Rowlands et al, 2022).…”
Section: Virtual Special Issue On CDImentioning
confidence: 99%
“…Payton et al (2023) reported the need for balance between structured and narrative forms of documentation and that highly structured formats (a feature of EHRs) can limit usability. Several authors highlighted multifactor influences on CDI, including personal, systemic and environmental (Jebraeily et al, 2023; Lövestam et al, 2022; Rowlands et al, 2022).…”
Section: Virtual Special Issue On CDImentioning
confidence: 99%